Analisis Kriminologi Dari Dampak Pelecehan Seksual Terhadap Anak Di Bawah Umur - Engracia, Levina Viola (Fakultas Hukum Universitas Wahid Hasyim, 2024)
The rise of cases of sexual abuse of minors continues to increase. Tanjungpinang is a capital in Riau Islands Province, Tanjungpinang is a growing city in this Province, Tanjungpinang city does not seem to be a friendly city for women and especially minors. Sexual abuse of minors can be either verbal or non-verbal. Children who experience such abuse will experience the impact of feeling humiliated for others. Sexual harassment is a harassing behavior or act committed by a person or group to others who are directly related to the party they are involved in and from these actions can reduce the dignity and self-esteem of someone they are offended. So it is necessary to improve child development, because besides being sensitive also during the growth period children need more love and attention from parents and family so that from this love and attention the needs and rights of children are basically fulfilled optimally. Children should be able to grow and develop into intelligent, moral and physically and spiritually healthy human beings. Because after all, children are the future leaders of the nation's successor, rights of the child are fundamentally fulfilled optimally. Children should be able to grow and develop into intelligent, moral and healthy human beings.Keywords: Sexual Abuse, Parenting, Child Rights, Tanjungpinang